Integrating ecosystem services in the assessment of urban energy trajectories – A study of the Stockholm Region. (January 2017) - Mörtberg, Ulla; Goldenberg, Romain; Kalantari, Zahra; Kordas, Olga; Deal, Brian; Balfors, Berit; Cvetkovic, Vladimir
Abstract: Urban development trajectories are changing towards compact, energy-efficient cities and renewable energy sources, and this will strongly affect ecosystem services (ES) that cities are dependent on but tend to disregard. Such ES can be provisioning, regulating and cultural ES, around which competition over land resources will increase with energy system shifts. Much of this can be foreseen to take place within urbanising regions that are simultaneously the living environment of a major part of the human population today. In order to inform critical urban policy decisions, tools for integrated assessment of urban energy and transport options and ecosystem services need to be developed. For this purpose, a case study of the Stockholm region was conducted, analysing three scenarios for the future urbanisation of the region, integrating a transport energy perspective and an ES perspective. The results showed that a dense but polycentric development pattern gives more opportunities for sustainable urban development, while the dense monocentric scenario has apparent drawbacks from an ES perspective. The methodology is compatible with a model integration platform for urban policy support and will thus enable integrated policy assessment of complex urban systems, with the goal of increasing their sustainability. Highlights: A diffuse urban pattern leads to low access to jobs and high energy consumption. A dense monocentric urban pattern implies high energy efficiency and low access to ES. A dense polycentric urban pattern allows for a combination of urban functions. ES needs to be integrated into sustainability assessments of urban policy options.